Applying claims analysis for detecting design flaws in interactive systems. - Suchetha Ravishankar. (2009)
The goal of any system design is to make sure that both experienced and novice users are able to make use of the system with ease, efficiency and effectiveness and the flexibility to interact with it in different ways and also to receive a good level of support from the system to achieve their goals. When users interact with a new system, they import their existing mental models and expect the new system to work in the same way as their mental models. Users may face problems if their existing mental models do not explain how to use a system. The goal of this dissertation was to apply Carroll's (2000) Claims Analysis to detect design flaws and usability problems due to mismatch in mental and design models in interactive systems taking Apple iPhone and Nokia N95 as examples. Carroll's (2000) Scenario Based Design and Claims Analysis is used to detennine the usability flaws of selected systems. Scenario-based design proposes a framework that allows usability to be inspected in the context of the users' different intended goals while Claims Analysis uses a schema that helps to surface conflicts among scenarios and enable designers to make decisions regarding design trade-offs and consequences. Sixteen usability heuristics and design guidelines, including Nielsen's usability heuristics, have been used as usability criteria to classify the design trade-offs and consequences.